Protective effects of recombinant lactoferrin with different iron saturations on enteritis injury in young mice - L.L. Fan; Q.Q. Yao; H.M. Wu; F. Wen; J.Q. Wang; H.Y. Li; N. Zheng (Journal of Dairy Science, 2022)
ABSTRACT: Infant intestinal development is immature and, thus, is vulnerable to bacterial and viral infections, which damage intestinal development and even induce acute enteritis. Numerous studies have investigated that lactoferrin (LF) has protective effects on the intestine and may play a role in preventing intestinal inflammation in infants. Lactoferrin is divided into 2 types, namely apo-LF and holo-LF, depending on the degree of iron saturation, which may affect its bioactivities. However, the role of LF iron saturation in protecting infant intestinal inflammation has not been clearly clarified. Therefore, in this study, young mice models with intestinal damage induced by lipopolysaccharides (LPS) in vivo and primary intestinal epithelial cells in vitro were constructed to enteritis injury in infants for investigation. The apo-LF and holo-LF were subsequently applied to the mouse models to investigate and compare their levels of protection in the intestinal inflammatory injury, as well as to identify which LF was most active. Moreover, the specific mechanism of the LF with optimal iron saturation was further investigated through Western blot assay. Results demonstrated that disease activity index, shortened length of colon tissue, and histopathological score were significantly decreased in the apo-LF group compared with those of the LPS group and the holo-LF group. In the apo-LF group, the concentration of LPS in the intestinal tract and the number of gram-negative bacteria colonies decreased significantly and the expression levels of proinflammatory factors in the colon tissue were downregulated, in comparison with those in the LPS group. The findings of this study thus verify that apo-LF can significantly alleviate enteritis injury caused by LPS, through regulating the PPAR-γ/PFKFB3/NF-κB inflammatory pathway.